Halal pharmaceuticals for pharmacists - Ahmad, Kausar (2014)
Standards Malaysia released the first ever guideline for the manufacturing of halal pharmaceuticals in the world which is the Malaysian Standard MS 2424:2010 (P). This is a new dawn for halal goods and services and especially pharmaceuticals because the authorities are actually acknowledging the need for halal pharmaceuticals. Will the use of this guideline enable manufacturers to obtain the JAKIM halal logo? The guideline can be referred to but the halal certification is another matter. In the past, providing the halal logo for pharmaceuticals is not a concern as the use of medicine is viewed as inevitable (or dharurah, in Arabic) especially for those suffering from critical illnesses. And yet in 2012, the authorities have given approval for over-the-counter medicines to bear the halal logo. Soon, the ubiquitous paracetamol tablets may have the halal logo on the packaging. This move is another indication of the pressing need from the Muslim consumers. With advances in technology, everything is possible - the non-halal porcine insulin can be substituted with humulin, obtained from recombinant DNA. Not all Muslim consumers are aware of the non-halal ingredients in pharmaceutical products and not all are aware that we do have halal alternatives for some products. We have vegetable capsules that can replace the probably non-halal bovine capsules. There is halal magnesium stearate processed from plants instead of non-halal animal fats; magnesium stearate is used rather widely in tableting. Dissemination of such information by all parties involved in providing the products to consumers is commendable. Although there is no move yet to qualify ethical products such as amlodipine as halal, consumers may ponder upon the philosophy of the manufacturer.